Athletes Friendly Education Handbook: Award for Educational Institutions supporting the Dual Career of Athletes - Ferjan, Marko; Jereb, Eva; Podbregar, Iztok; Robnik, Petra; Šprajc, Polona; Thaler, Mathias; Šolar, Aleš (University of Maribor Press, 2021)
(AFE) is a type of schooling, continually planning, organizing, and improving a system of adaptations included in a school’s educational process and infrastructure. These adaptations are implemented voluntarily and in a benevolent, systematic, comprehensive, and transparent manner, with the explicit aim to help athletes engage in sport and simultaneously achieve goals and competencies set out in the educational program and thus Athlete friendly education has the following attributes: adaptations; rather than being discrete, these adaptations constitute a system; daptations are organized and managed by school management; institutions introduce the adaptations voluntarily; adaptations are based on pre-existing legal frameworks and internal institutional regulations; institutions need to possess adequate competencies or experience; they need to be "trustworthy," in other words. AFE accreditation is voluntary. The principle of voluntary certification is very similar to the "brand" philosophy. The brand also contains a "promise."